2018
DOI: 10.3390/app9010116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Temperatures on Bletillae Rhizoma Polysaccharide Extraction and Physicochemical Properties

Abstract: Six fractional polysaccharides were prepared by water extraction and alcohol precipitation under controlled temperature from bletillae rhizoma, a traditional Chinese medicine. Based on this, yields of bletillae rhizome polysaccharides (RBPs) were obtained. The extracting temperature impacted the characteristics of the fractional polysaccharides. The fractional polysaccharides were characterized by glucomannan (GM) content, thermal stability, scanning electron microscopy (SEM), Fourier-transform infrared (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Enzymatic hydrolysis of KGM caused slight changes in the range of 1200–1500 cm −1 related to amine groups and 3400–3450 cm −1 associated with glycosidic and hydroxyl bonds. Prolonged enzymatic hydrolysis was responsible for more pronounced amine and O–H bands, due to the breakdown of glycosidic bonds (Long et al ., 2018; Cortez‐Trejo et al ., 2022; Makshakova & Zuev, 2022). In addition, it can also be found that the prolonged enzymatic time weakened the band intensity at 1723 cm −1 from the acetyl groups, indicating that the molecular structure of KGM changed with hydrolysis treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic hydrolysis of KGM caused slight changes in the range of 1200–1500 cm −1 related to amine groups and 3400–3450 cm −1 associated with glycosidic and hydroxyl bonds. Prolonged enzymatic hydrolysis was responsible for more pronounced amine and O–H bands, due to the breakdown of glycosidic bonds (Long et al ., 2018; Cortez‐Trejo et al ., 2022; Makshakova & Zuev, 2022). In addition, it can also be found that the prolonged enzymatic time weakened the band intensity at 1723 cm −1 from the acetyl groups, indicating that the molecular structure of KGM changed with hydrolysis treatments.…”
Section: Resultsmentioning
confidence: 99%